Relationship Between the Job Market and Performance in the Accounting Proficiency Exam - Santana, Daysi Leal de; Oliveira, José Sérgio Casé de (Advances in Scientific and Applied Accounting, 2025)
Objective: This study investigates whether the economic condition of the labor market influences performance in the Accounting Proficiency Examination (APE). Method: Academic performance is presented as a percentage pass rate with threshold values of 0 and 1. The proxies for the market condition are the number of accounting organizations (ORG) and the average accounting salary (AAS). Inflated beta regression models were used to analyze data from two editions of the Accounting Examination in 2018. Results: The findings indicate that the condition of the labor market influences the Pass Rate in the Accounting Sufficiency Exam, a promising discussion about academic performance, in addition to the characteristics of the educational institutions. In addition, the Enade concept and the HEI category proved to be influential in terms of the occurrence of 0 in Pass Rate. However, no significant variables were identified for the occurrence of 1. Contributions: Besides the labor market being pointed out as an incentive for professional choice, the study adds to the literature on the relationship between the labor market and performance at the APE. It also suggests an integrated dialogue between accounting councils, HEIs and business organizations to strengthen relations between accounting education and training and increase the pass rate.